RELASI GENDER KELUARGA BURUH PANEN CENGKEH PT. SUMBER SARI PETUNG DI DUSUN SUMBER PETUNG DESA SEMPU KECAMATAN NGANCAR KABUPATEN KEDIRI (Agridevina : Berkala Ilmiah Agribisnis, 2022)
There is a double workload and stereotypes that arise in clove harvest workers in PT. Source of petung essence. The purpose of the study was to analyze the gender relations found in the families of clove harvest workers and calculate the contribution of clove harvest workers to the families of PT clove workers. Sumber Sari Petung in Sumber Petung Hamlet, Sempu Village, Ngancar District, Kediri Regency. the method used is qualitative which is descriptive in the formulation of the first problem and quantitative with descriptive statistics. The gender relations of the clove-harvest workers' families resulted in gender injustice in the form of a double workload on the wives of picked laborers and laborers. Doing reproductive work which is a responsibility based on the partiarti culture that developed in Sumber Petung Hamlet and had to work in the productive sector to help meet the needs of the family. There is a gender injustice in the form of stereotypes in the form of wage gaps in picking and pitil workers, where pitil workers get less wages than picking workers who are considered easier. The contribution contributed by clove harvest workers during the harvest season is 9% smaller with a wage of Rp. 2,422,833.33/month compared to doing other work to 42% with a wage of Rp. 10,797,666.66/month. DOI : https://doi.org/10.33005/adv.v11i1.3156